PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN RPP DAN PELAKSANAAN PEMBELAJARAN MELALUI TEKNIK IHT (IN HOUSE TRAINING) - Heni Ribut Handayani (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
The purpose of this study was to improve teacher competence in organize the lesson plan (RPP) and learning procces by conducting in house training (IHT) among the teachers at Imogiri state elementary school (SD N Imogiri). The study was a class action research with Kemmis and Mc.Taggart model. Subjects of the study were teachers at SD N Imogiri, Bantul regency, special province of Yogyakarta. Data collected by using interview, questionnaire, and class supervision that furthermore analyzed using the quantitative descriptive approach and conduced in planning, implementation, observation, and reflection, respectively. Results of the study show that the in house training may improve teacher’s competence in organize the lesson plan and learning procces. Initial condition indicate less quality of learning procces. The average rate in Cycle I was 70.58 with 29.41% completeness. Thus improve in Cycle II with average rate of 89.41 and 100% completeness. The learning implementation was in low category at initial condition (Cycle I) that showed average rate of 72.94 and 38.82% completeness. Nevertheless it increased in Cycle II that indicated the average rate of 88.82 and 100% completeness.